Research progress on antidepressant effects and mechanisms of berberine - Gao, Yang; Nie, Kexin; Wang, Hongzhan; Dong, Hui; Tang, Yueheng (Frontiers in Pharmacology, 2024)
Depression, a global health problem with growing prevalence, brings serious impacts on the daily life of patients. However, the antidepressants currently used in clinical are not perfectly effective, which greatly reduces the compliance of patients.Berberine is a natural quaternary alkaloid which has been shown to have a variety of pharmacological effects, such as hypoglycemic, lipid-regulation, anti-cancer, antibacterial, anti-oxidation, anti-inflammatory, and antidepressant. This review summarizes the evidence of pharmacological applications of berberine in treating depression and elucidates the mechanisms of berberine regulating neurotransmitter levels, promoting the regeneration of hippocampal neurons, improving hypothalamicpituitary-adrenal axis dysfunction, anti-oxidative stress, and suppressing inflammatory status in order to provide a reference for further research and clinical application of berberine.